2004
DOI: 10.1038/nn1280
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated multivesicular release at a mammalian ribbon synapse

Abstract: Traditional models of synaptic transmission hold that release sites within an active zone operate independently. Although the release of multiple vesicles (multivesicular release; MVR) from single active zones occurs at some central synapses, MVR is not thought to require coordination among release sites. Ribbon synapses seem to be optimized to release many vesicles over an extended period, but the dynamics of MVR at ribbon synapses is unknown. We examined MVR at a ribbon synapse in a retinal slice preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
255
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(279 citation statements)
references
References 46 publications
22
255
0
Order By: Relevance
“…In contrast, the RRP estimate from ⌬C m measurements in mouse inner hair cells is Ϸ53-64 SVs per synapse, whereas the morphologically docked SV pool contains only [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Some of this difference may be due to the fact that synaptic exocytosis had not been inhibited before fixation, which in frog saccular hair cells reduced the number of docked SVs per synapse from 43 to 32 (11).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the RRP estimate from ⌬C m measurements in mouse inner hair cells is Ϸ53-64 SVs per synapse, whereas the morphologically docked SV pool contains only [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Some of this difference may be due to the fact that synaptic exocytosis had not been inhibited before fixation, which in frog saccular hair cells reduced the number of docked SVs per synapse from 43 to 32 (11).…”
Section: Discussionmentioning
confidence: 99%
“…2D). Compound vesicles have been observed in non-neuronal secretory cells (e.g., Alvarez de Toledo and Fernandez, 1990) and could potentially underlie the multivesicular release reported in bipolar cells (Singer et al, 2004) and cochlear hair cells (Glowatzki and Fuchs, 2002;Edmonds et al, 2004). On the other hand, it is difficult to reconcile the fusion of compound vesicles with the rise in membrane capacitance evoked by the rapid, global elevation of calcium, which is best described by a smooth, single exponential function indicative of the fusion of a small, homogeneous class of vesicle (Heidelberger et al, 1994).…”
Section: Fusion Scenarios and Ribbon Functionmentioning
confidence: 99%
“…As with the Mb 1 bipolar cell, the intensity of the stimulus determines the relative ratios between the transient and sustained components. These two components share similar sensitivities to exogenous calcium buffers and may represent the fusion of vesicles located near calcium channels (Singer et al, 2004). Thus, there could potentially be release during the plateau phase, depending upon stimulation intensity.…”
Section: Relation Of Synaptic Release To the Underlying Light-evoked mentioning
confidence: 99%
“…At the EM level, the presynaptic elements are classical ribbon synapses (Kolb 1979;Sterling et al, 1988;Strettoi et al, 1990Strettoi et al, , 1992. The synaptic input is mediated by iGluRs of the AMPA-type (GluARs) (Singer and Diamond, 2003;Singer et al, 2004;Veruki et al, 2003 and immunocytochemical studies have identified the presence of GluA2/3 and GluA4 AMPA receptor subunits postsynaptically (Ghosh et al, 2001;Li et al, 2002). A recent study suggests that AII amacrines may also receive input at the arboreal dendrites from ribbon synapses of one type of ON-cone bipolar cell (Anderson et al, 2011).…”
Section: The Aii Amacrine Cell In the Mammalian Retinamentioning
confidence: 99%